2018
DOI: 10.7554/elife.35314
|View full text |Cite
|
Sign up to set email alerts
|

The newly-arisen Devil facial tumour disease 2 (DFT2) reveals a mechanism for the emergence of a contagious cancer

Abstract: Devil Facial Tumour 2 (DFT2) is a recently discovered contagious cancer circulating in the Tasmanian devil (Sarcophilus harrisii), a species which already harbours a more widespread contagious cancer, Devil Facial Tumour 1 (DFT1). Here we show that in contrast to DFT1, DFT2 cells express major histocompatibility complex (MHC) class I molecules, demonstrating that loss of MHC is not necessary for the emergence of a contagious cancer. However, the most highly expressed MHC class I alleles in DFT2 cells are commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…At a minimum, we predict that fibroblasts have six allotypes at the cell surface and DFT1+IFNg and DFT2 have 3 and 5 functional allotypes respectively. These alleles correlate well with our previous definition of the MHC-I transcripts expressed by DFT1+IFNg and DFT2 and fibroblasts(1). However, there are a number of exceptions.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…At a minimum, we predict that fibroblasts have six allotypes at the cell surface and DFT1+IFNg and DFT2 have 3 and 5 functional allotypes respectively. These alleles correlate well with our previous definition of the MHC-I transcripts expressed by DFT1+IFNg and DFT2 and fibroblasts(1). However, there are a number of exceptions.…”
supporting
confidence: 89%
“…However, rare instances of spontaneous DFT1 tumour regression have been described and vaccination and immunotherapy of devils with live MHC-I positive DFT1 cells demonstrate that devils can mount an effective immune response against the disease in some instances (19)(20)(21). We have 5 recently shown that in contrast to DFT1, DFT2 cells express MHC-I molecules, but the expressed alleles are similar between hosts and tumours in the samples analysed (1).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We acknowledge that a larger sampling effort in areas north of the peninsula is necessary to firmly conclude that DFT2 has not escaped the confinement Another plausible explanation is the difference in MHC class I expression between both tumours. There is evidence that DFT2 cells express classical and non-classical MHC alleles, which is likely to lessen the immunogenicity of tumour cells and reduce susceptibility infection (Caldwell et al, 2018). However, the expression of MHC molecules in DFT2 is not uniform and, given its early stage of evolutionary history, is possible that it might be gradually lost, facilitating a possibly higher rate of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that the DFT1 cells downregulate MHC class I (MHC-I) expression 19 , a phenomenon observed in many human cancers 20 . In contrast to DFT1 cells, the DFT2 cells do express MHC-I 21 . DFT1 and DFT2 cells also have 2,884 and 3,591 single nucleotide variants, respectively, that are not present in 46 normal devil genomes 22 .…”
Section: Introductionmentioning
confidence: 84%